Teaching Hospital Information Systems by Simulating What Really Happens - Protti, D. J. (Methods of Information in Medicine, 1989)
This paper discusses the teaching of a course which simulates what a hospital goes through when it conceptualizes the need for a Hospital Information System, identifies its goals and objectives for the system, prepares a Request for Proposal (RFP), and selects a particular system. The course is. taught entirely in simulation and role playing modes. Students are taken on site visits, vendors come to the University to demonstrate their systems, and consultants are brought in to give advice. The pros and cons of this particular style of teaching are discussed.
Keywords: Hospital Information Systems; Computer System Procurement; Attitudes towards Computers